Penerapan Human Centered Technology untuk Ekosistem Pertanian Digital Berkelanjutan di Desa Sei Penjara, Kecamatan Sei Bingai, Kabupaten Langkat - Buaton, Relita; Luta, Devi Andriani; Selfira, Selfira; Prahmana, I Gusti (Universitas Dinamika, 2026)
Technology implementation in rural areas often faces sustainability challenges due to a lack of user focus. In Sei Penjara Village, specific problems were identified in inefficient, high-risk agricultural management, and a high dependence on a single individual. To address these issues, this program adopted a Human Centered Technology approach through a two track strategy that integrates the development of Internet of Things (IoT) hardware for precision agriculture with human resource empowerment through digital marketing training. The implementation method is through technology design and preparation, including the design of soil and water nutrient monitoring tools, application development, and implementation, installation, and training on the use of IoT tools, sensors, and applications. The results in the field show that the results of community service activities have a real, direct, and measurable impact on increasing the capacity of village communities, the application of IoT-based soil and water nutrient monitoring tools has been proven to increase fertilization efficiency by ± 25% and reduce agricultural operational costs by around 35%, more than 80% of training participants are able to use ChatBot independently, participants are able to produce promotional content independently, understand product storytelling strategies, and utilize social media analytics features to reach a wider market, and the next stage plan is to monitor the development of the impact of the IoT tools produced in optimizing community harvests. If there are obstacles, they will be evaluated, but if there are no obstacles, this program will be implemented in villages in Langkat Regency and its surroundings.